Análise do envolvimento do Fator Neutrófico Derivado do Cérebro (BDNF) e do metabolismo glicolítico cerebral através do escaneamento com microPET na disfunção cognitiva induzida pelo acúmulo de ferro cerebral - Alcalde, Luisa Azambuja (2017)
Brain-derived neurotrophic factor (BDNF) is the most abundant neurotrophin in the mammalian Central Nervous System, and plays a key role in development and physiology, as well as in pathological states. Post-mortem studies demonstrated that BDNF levels are reduced in the brains of patients affected by neurodegenerative diseases, such as Alzheimer’s disease (AD). Iron accumulation has consistently been associated to the pathogenesis of neurodegenerative diseases. In rats, neonatal iron overload induces memory deficits, and increases oxidative stress and apoptotic markers, and decreases the expression of the synaptic marker, synaptophysin. Deferiprone (DFP) is an oral iron chelator used for the treatment of systemic iron overload disorders, and has recently been tested in Parkinson’s disease patients. Here, we aimed to determine the effects of iron overload on BDNF levels and glucose metabolism, measured by 18FDG uptake using positron emission tomography. Moreover, we intended to characterize the effects of DFP on iron-induced memory deficits and BDNF levels, as well as on glucose metabolism. Rats received iron or vehicle at postnatal days 12-14 and when adults, received chronic DFP or water. Recognition memory was tested 19 days after the beginning of chelation therapy. 18FDG uptake was performed 24 h after the last day of treatment. Another subset of animals was sacrificed 24 h after the last day of treatment for BDNF measurements, and TrkB and p75 expression analysis. DFP was able to restore memory impairment and increase hippocampal BDNF levels, ameliorating iron-induced effects. The present findings support the use of DFP in clinical trials including AD patients.